Effects of the Kuroshio on internal tides in the Luzon Strait: A model study - Tang, Guoqin; Deng, Zengan; Chen, Ru; Xiu, Fangrui (Frontiers in Marine Science, 2023)
Internal tides have a great impact on the meridional overturning circulation and climate variability through contributing to diapycnal mixing. The Luzon Strait (LS) is one of the most important sites of internal tide generation in the global ocean. In this study, we evaluate the effect of the Kuroshio on the M2 and K1 internal tides in both summer and winter seasons in the South China Sea (SCS), particularly within the LS. High-resolution ocean numerical simulations with the Kuroshio Current were compared with those without. We found that the Kuroshio has negligible impact on the generation site of internal tides. Compared to seasonal variability in the total barotropic to baroclinic conversion rate over the LS, the Kuroshio has relatively little influence. However, the Kuroshio flow strongly guides the propagating direction of the internal tides from the LS into the SCS. The Kuroshio also substantially decreases the southward energy fluxes going out of the LS. For both M2 and K1 tides, turning off the Kuroshio leads to a weaker energy exchange between the background shear and internal tides. Turning off the Kuroshio also weakens the divergence of internal tide energy due to the advection of background flow. Thus, our results reveal a non-negligible effect of the Kuroshio on the internal tides in the LS. If one aims to realistically simulate, or better understand, internal tides, these results indicate that one should include realistic oceanic circulation fields.